The Optical Approaches to Monitor Biomass Ethanol Productions with Optical Microscopic Methods - Huipeng Gao; Xiaoxiao Li; Xianting Zhang; Rui Li; Hsiang-Chen Chui; Quan Zhang (Photonics)
Oil and natural gas continue to dominate global energy consumption, though a supply gap of 2 million barrels per day (b/d) was reported in the fourth quarter of 2023. Despite a projected increase in global oil supply by 1.2 million b/d in 2023, reaching 101.1 million b/d compared to 2022, reliance on fossil fuels poses challenges for energy security and sustainability. For China, transitioning to clean and renewable energy sources is essential. Biofuel ethanol, with its high octane rating and anti-knock properties, is a promising alternative. This bioenergy sector is expanding globally, with cellulosic ethanol production emerging as a key objective. However, the high production cost of cellulosic ethanol presents a significant challenge to its large-scale adoption. To overcome this barrier, various techniques are being explored to reduce production costs. Among them, advanced characterization methods are used to monitor changes in cellulose, lignin, and hemicellulose during ethanol production in situ, quickly and without surface labeling. These methods provide insights into the factors driving high production costs, enabling targeted improvements. This review focuses on the potential of these characterization techniques to optimize ethanol production processes and improve efficiency. The findings may offer a strategic direction for scaling up cellulosic ethanol production and contribute to the sustainability of energy resources by reducing dependency on fossil fuels.